Emancipación o Metamorfosis: Consecuencia postcolonial de la Trata Negrera de la Esclavitud - Nelson Aboy Domingo (Comparative Cultural Studies, 2018)
The postcolonial emancipation in Africa implies the insertion of ethnos elements into the dominant cultural system. The slaves rescued by the British Navy during the legal Trade were multiple and dissimilar to between them concentrated in coastal cities that can not subsist in particular minorities, also, the need for social integration; and they were, in turn, incompatible and incompetent in the face of British and learned culture. The British were schooled in English and converted to Christianity, as part of the “civilizing” process. So, they substituted each and every one of their diverse cultural and religious identities, for an ethnocultural colonial invention, that granted official weight and that since then was denominated: Yoruba, to all the emancipated ones concentrated in the British colonial demarcation of Yorubaland (Yoruba Earth). Because of the relevance and egocentrism that the official British discourse of the time gave to this fallacy of the African indigenous tradition, in the last decades (1980-2010) it has migrated to America and other latitudes, for the purpose of a new colonization of the cultural identities of African antecedents that are conserved in the African-American diasporas and, paradoxically, they call themselves: Yoruba traditionalists, as false bearers of the oldest autochthonous traditions of the original ancestral cultures. The present material tries to locate historical facts and events that clarify the colonial origin of this human conglomerate, which call themselves Yorubas; at the same time, to demonstrate that they are only carriers of the egocentric and colonizing pattern of cultural thought, which since then they inherited from the metamorphosis they suffered, rather than from a real emancipation and conservation of their ancestral cultures.